Peranan Sucrose Phosphate Synthase (SPS) dan Acid Invertase (AI) Internoda Tebu (Saccharum officinarum L.) dalam Akumulasi Sukrosa - -, MISWAR; SUGIHARTO, BAMBANG; HANDOYO, TRI; AYU MADE, SRI (AGRITROP, 2012)
Sucrose content is an important component of yield in sugarcane (Saccharum officinarum L.) juice and its synthesis is determines by the activity of Sucrose phosphate synthase (SPS; EC. 2.4.1.14). This enzyme catalyzes the penultimate reaction of the formation of sucrose from fructose-6-phosphate (F6P) and uridine-5-diphospho glucose (UDPG). Sucrose is synthesized on leaf and translocated into stalk at where it is accumulated to be accumulated it. In contrast to SPS, acid invertase (AI) is an enzyme that hydrolyze sucrose to glucose and fructose. The ability of sugarcane to accumulate the sucrose in stalk is determined by the differences between SPS and AI activities. This study was aimed know role of the internodes SPS and AI in sucrose accumulation in the internodes of some sugarcane varieties. SPS, AI and sucrose were extracted from internodes 1, 3 and 5 of 9 month old sugarcane. The results showed that sucrose content for all varieties increased concomitant with the rise in the age of internodes. The decrease in AI activity in internode caused the increase in sucrose content in internodes. Meanwhile, higher sucrose content in the older internodes was not followed by higher in SPS activity. Generally, there was strong negative correlation between sucrose content of internodes with SPS and AI activity. In conclusion, the ability of sugarcane to accumulate sucrose at internodes was primary determined by AI activity, while SPS activity had a small role on sucrose accumulation at internodes.
Keywords: sugarcane, sucrose phosphate synthase, acid invertase, sucrose, internodes